Description and ecology of a new species of Eriopeltastes Burmeister & Schaum, 1840 (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini), from KwaZulu-Natal, South Africa - Ricchiardi, Enrico; Perissinotto, Renzo (Zootaxa, 2013)
A dedicated “Bioblitz” survey of the Ntinini Nature Reserve was organized and coordinated by Ezemvelo KwaZulu- Natal (EKZN) Wildlife, during the period 16–18 November 2010. The main aim of the Bioblitz was to provide biodiversity data that could assist in assessing the necessity of a formal proclamation for the protection of the reserve, within the scope of the integrated Biodiversity Conservation Planning of EKZN Wildlife